Analysis of the Main Female Characters in the Melur for Firdaus Web Series and Their Implementation in Learning - Asyari, Efrilian; Hariadi, Try; Hajjafiani, Dini (Jurnal Pendidikan Amartha, 2023)
This study aims to describe the analysis of the main female character in the web series Melur untuk Firdaus and its implementation in learning at SMP Negeri 23 Pontianak. The methods and forms of research used are descriptive methods and qualitative research forms, and use a feminist approach. The data in this study are in the form of words and quotes that contain the roles and positions of women, gender injustice, and women's struggles in the web series. The data source used in this study is the Melur web series for Firdaus which aired on Slot Lestary TV3 on May 27 2022 with a total of 28 episodes. Data collection techniques used in this research are documentary study techniques and observational techniques. The data collection tool used by the researchers themselves as the main instrument and data card and assisted by observation guidelines. The data analysis technique used is content analysis technique. The results of the analysis obtained from this research are the role and position of women as children and also wives, gender injustice in the form of marginalization, stereotypes, and violence, as well as women's struggles in maintaining their household and its implementation in learning at SMP Negeri 23 Pontianak. The roles and positions in Melur's web series for Firdaus are divided into two. First, it describes the role and position of women as children who carry out their obligations to help with household chores, respect and care for their parents. Second, the role and position of women as wives who carry out their obligations, namely respecting, caring for, fulfilling and serving the needs of their husbands. There are three forms of gender injustice, namely marginalization that women are considered insignificant in making decisions and are only used as sex slaves, stereotypes limiting women from interfering and labeling in the form of insults, as well as physical and non-physical violence and its implementation in learning at SMP Negeri 23 Pontianak.